Importancia del consumidor para el estado peruano, una mirada desde el enfoque constitucional - Chocano Ravina, Eduardo Jesús (2025)
From the standpoint of economic constitutionalism, the social market economy requires institutions that guarantee equitable access to the market, which presupposes effective consumer protection. The consumer is not a passive subject, but the agent that achieves the goals of the constitutional economic model: efficiency with justice and competition with equity. Its recognition as a subject of rights implies that guarantees such as information, safety and redress must be read as fundamental rights. In this context, state intervention does not contravene freedom of enterprise, but acts as a constitutional guarantee to preserve the purposes of the market. The information asymmetry between supplier and consumer is not only an economic problem, but a conflict of power that compromises substantive equality. Therefore, the State not only can, but must intervene to correct these imbalances through regulation, supervision and sanction, thus strengthening a fair and constitutionally legitimate market.